Dampak Medan Magnet terhadap Karakteristik Pembakaran Tetesan Minyak Kelapa - Wigo Winarko; Yuke Hary Laksono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Improving the combustion efficiency and stability of biofuels such as virgin coconut oil (VCO) is a major challenge in renewable energy development. This study aims to investigate quantitatively the effect of external magnetic field configuration on the freezing dynamics of single VCO droplets. The experiment was performed using combustion of a single droplet placed on a thermocouple that also functions as a temperature meter. To generate a flame, the droplet was heated using a heating element until it ignites. The VCO droplets were burnt under five conditions: without a magnetic field (WOM), and between two permanent magnets with four different pole configurations, attractive (N-S, S-N) and repulsive (N-N, S-S). The observation included flame morphology, temperature profile, flame height, burning rate, and ignition delay time. Results showed that the magnetic field significantly improves combustion performance. The flicker instability due to buoyancy can be eliminated, while the peak temperature increases from 761 °C in the WOM condition to 858 °C in the S-N configuration. Furthermore, the combustion rate increased, and the ignition delay time decreased from 4.99 s (WOM) to 3.43 s (N-S/S-N). Consistently, the attractive field configuration (N-S/S-N) yielded the best performance. These findings confirm that the magnetic field orientation serves as a key parameter to control the dynamics and enhance the combustion intensity of biofuels.